Enhancement of the underground cable current capacity by using nano‐dielectrics - Ossama E. Gouda; Mohamed M. F. Darwish; Ahmed Thabet; Matti Lehtonen; Gomaa F. A. Osman (Energy Science & Engineering)
Abstract In most underground power cables, cross‐linked polyethylene (XLPE) is utilized as the main insulating material, while polyvinyl chloride (PVC) is usually used as a nonmetallic sheath or jacketing for the cable. Accordingly, improving the electrical and thermal characteristics of these materials leads to an increase in cable dielectric strength, besides a rise in the current capacity of the underground power cables. Thus, enhancing the thermal characteristics of cable insulation is the goal of many research studies. In this regard, increasing the current capacity of underground power cables is an essential topic for electrical distribution and transmission networks. This usually occurs by increasing the cross‐sectional area of the cable conductor, which means raising the cost of transmitting electrical energy. Another proposed alternative may be to improve the thermal properties of the dielectric material using nanotechnology to allow better dissipation of heat resulting from the cable losses. This article proposes the use of nano‐composite dielectrics to increase the current capacities of underground power cables. Nano‐fillers are used to enhance the thermal and electrical characteristics of XLPE and PVC, which represent cable dielectric materials. Accordingly, in this paper, many experiments are conducted on various nano‐dielectric materials to choose the most appropriate nano‐dielectrics for improving both the thermal and electrical properties. Hence, measurements are performed on the thermal and electrical properties of dielectric nano‐materials manufactured in the laboratory. Further, calculations of the cable's current capacities by the use of the measured properties of nano‐dielectrics are done considering several backfill soils. From the obtained measurements and calculations carried out on cable capacities, it is concluded that the use of XLPE/ZnO 5 wt.% as the insulation and PVC/ZnO 5 wt.% as the jacket material increased the cable current capacity by 6.2% for a cable of 33 kV rating, 9.2% for 66 kV cable, and 15.7% for 220 kV cable when wet clay is used as backfill soil. From the calculations carried out it is found that the use of nano‐composite dielectrics reduces the temperature of the cable components by significant values. For example, the core temperature of the 33 kV cable is reduced by 15.6°C, while for the 66 kV cable, the cable core temperature is decreased by 12.6°C, and for 220 kV the conductor temperature is reduced from 71.3°C to 58.3°C when each cable is loaded by its rating.